Penentuan Konsentrasi Aktivator Asam Sulfat Terbaik pada Pretreatment Zeolit Alam Lampung (Zal) sebagai Katalisator untuk Reaksi Esterifikasi Gliserol dan Asam Asetat Menjadi Triacetin - Achmad Ariyadi; Simparmin Br. Ginting (Balitbangda Provinsi Lampung, 2017)
The research has been done to obtain the best concentration of sulfuric acid activator on Lampung Natural Zeolite at the pretreatment stage as catalyst for esterification reaction of glycerol and acetic acid to form triacetin. The process of pretreatment was chemical activation where the zeolite wasimmersed in sulfuric acidina concentration of 0.2; 0.3and 0.4 N. The zeolite activation results were analyzed for the SiO2/Al2O3 ratio with XRF analysis. Then the three pretreated zeolites with variations of the activator concentration were tested for performance as catalysts for the reaction of triacetin formation from glycerol and acetic acid with the reaction time of 90 minutes and the sampling for every 15 minutes. The samples were then compared with the reactions using zeolite catalyst without activation and the reactions without catalyst. The highest and best conversion was obtained on pretreated zeolite catalyst 0.2 N sulfuric acid with conversion of 11.75 %. The XRF analysis resulted that higher the concentration of sulfuric acid activator, higher the ratio of SiO2/Al2O3 zeolite. The FTIR analysis showed that the activation treatment on zeolite did not cause significant changes in its structures.